2017
DOI: 10.3389/fbioe.2017.00025
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Blood and Lymphatic Microvascular Networks in Fibrin Matrices

Abstract: Vascular network engineering is essential for nutrient delivery to tissue-engineered constructs and, consequently, their survival. In addition, the functionality of tissues also depends on tissue drainage and immune cell accessibility, which are the main functions of the lymphatic system. Engineering both the blood and lymphatic microvasculature would advance the survival and functionality of tissue-engineered constructs. The aim of this study was to isolate pure populations of lymphatic endothelial cells (LEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 64 publications
2
70
1
Order By: Relevance
“…This cell type has been extensively used in in vitro angiogenesis models in the literature (Bayer, Fedorchak, & Little, ; Freiman et al, ; Xiao et al, ) and in previous publications from our group (Lloyd‐Griffith et al, ; McFadden et al, ) and remains the most studied endothelial cell type due to its availability and ease of isolation and culture (Morin & Tranquillo, ). Nevertheless, we acknowledge that other endothelial cell types isolated from adult donors and not umbilical vein could be explored in future iterations of this work, such as human dermal microvascular endothelial cells (Cui & Boland, ) and human blood vascular endothelial cells (Knezevic et al, ), which may better mimic microvascular features.…”
Section: Discussionmentioning
confidence: 99%
“…This cell type has been extensively used in in vitro angiogenesis models in the literature (Bayer, Fedorchak, & Little, ; Freiman et al, ; Xiao et al, ) and in previous publications from our group (Lloyd‐Griffith et al, ; McFadden et al, ) and remains the most studied endothelial cell type due to its availability and ease of isolation and culture (Morin & Tranquillo, ). Nevertheless, we acknowledge that other endothelial cell types isolated from adult donors and not umbilical vein could be explored in future iterations of this work, such as human dermal microvascular endothelial cells (Cui & Boland, ) and human blood vascular endothelial cells (Knezevic et al, ), which may better mimic microvascular features.…”
Section: Discussionmentioning
confidence: 99%
“…That study showed that the expression of angiogenesis related genes (VE-cadherin, VEGFR2) and proteins (VEGF, FGF, Ang-1) was higher in ASCs/HUVECs co-culture compared to pure HUVECs culture [106]. ASCs have also been shown to be critical for vascular network formation from blood vascular and lymphatic endothelial cells [120].Studies on human dermal microvascular endothelial cells have revealed the role of VEGF in specialization of the tip endothelial cells and their directional migration to form capillary-like structures [121]. Similarly, inducing the Notch signalling pathway upregulated VEGF-A, VEGF-B and VEGF-R1 expressions, and promoted vascular network formation in co-cultured mouse brain microvascular endothelial cells and ASCs in 3D collagen type-I gel [122].…”
Section: Culture Of Vascular Network Using Endothelial Cellsmentioning
confidence: 98%
“…A number of in vitro studies have focused on probing for the specific functions of signaling molecules. For example, Knezevic et al formed lymphatic and blood vessel networks to interrogate the effects of VEGF‐C and ASC, demonstrating the necessity of cell‐cell contact between LECs and ASC to form microvascular networks . In addition, Gibot et al successfully developed a stable 3‐D lumen‐containing lymphatic capillary networks by co‐culturing LECs with fibroblasts on sheets of tissue‐engineered skin substitutes .…”
Section: Lymphatic Vessel Physiology Function and Lymphangiogenesismentioning
confidence: 99%